11.3d+2.5=1.3d

Simple and best practice solution for 11.3d+2.5=1.3d equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11.3d+2.5=1.3d equation:


Simplifying
11.3d + 2.5 = 1.3d

Reorder the terms:
2.5 + 11.3d = 1.3d

Solving
2.5 + 11.3d = 1.3d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-1.3d' to each side of the equation.
2.5 + 11.3d + -1.3d = 1.3d + -1.3d

Combine like terms: 11.3d + -1.3d = 10d
2.5 + 10d = 1.3d + -1.3d

Combine like terms: 1.3d + -1.3d = 0.0
2.5 + 10d = 0.0

Add '-2.5' to each side of the equation.
2.5 + -2.5 + 10d = 0.0 + -2.5

Combine like terms: 2.5 + -2.5 = 0.0
0.0 + 10d = 0.0 + -2.5
10d = 0.0 + -2.5

Combine like terms: 0.0 + -2.5 = -2.5
10d = -2.5

Divide each side by '10'.
d = -0.25

Simplifying
d = -0.25

See similar equations:

| 4(-7-6n)=-268 | | 2(3+4a)=-42 | | 7(-4k+6)=-182 | | 3(2+7a)=195 | | -2x-4=-9 | | 6-3(3x-2)=15 | | 2(-1)-3y=18 | | 4(5-b)=24 | | 6(-5+7d)=-30 | | 2(-2)-3y=18 | | 5(1a+6)=30 | | b-14.72=18.45 | | 4(4+3m)=16 | | 2(-5n+4)=-62 | | -20+x=x+16 | | 7(9+3m)=168 | | 4(-6t-1)=-148 | | 2(7-2t)=42 | | 3(9-2d)=3 | | df=g-10 | | 6(-2t+8)=-84 | | 7(-5+n)=-28 | | 4(2+a)=44 | | 6(2a+10)=96 | | 5(5+6n)=-215 | | 15a-54=-3 | | 7(-5+3k)=175 | | an=3+(n-1)(-5) | | (2x+10)=(86+x) | | 81=.5(9)h | | 76+x=180 | | X+7X-6=20 |

Equations solver categories